STUDY OF MORBIDITY PATTERN IN GERIATRIC POPULATION AND CORRELATION OF HOUSING CONDITIONS WITH RELEVANT MORBIDITIES IN A RURAL AREA OF KANPUR - Goel, S; Srivastava, V K; Nigam, Seema; Saxena, S C; Varma, Punit; Sharma, R P (Indian Journal of Community Health, 2008)
.